Developing optimized strengthening systems for shear‐deficient concrete members. (9th August 2017) - Randl, Norbert; Harsányi, Peter
Abstract : Strengthening methods for shear‐deficient bridges were developed and tested in cooperation with the HILTI Corporation and SIKA Austria. In order to identify the strengthening effect in shear, a number of 12 T‐shaped RC‐beams with a length of 5.38 m were designed. In the experimental campaign two different types of strengthening systems were applied and subjected to shear loading until failure. The successful use of a modern digital image correlation system provided the basis for an in‐depth analysis of failure mode and crack pattern as well as shear degradation at each load stage. Finally, the applicability of existing shear design models with consideration of the strengthening elements analogously to cast‐in shear reinforcement was evaluated.